Pengaruh Faktor-Faktor Perpajakan terhadap Model Manajemen Laba Stubben: Peran Corporate Governance sebagai Pemoderasi - Guna, Welvin I; Trisnawati, Estralita (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2024)
The manner in which enterprises in Indonesia administer their profits has been profoundly influenced by modifications in tax legislation, particularly since the enactment of the Harmonisation of Taxation Law (UU HPP). Moreover, the Covid-19 pandemic is presently advancing in its trajectory. New incentives are created for managers to manipulate income in order to reduce their tax obligations by the redesigned tax code. Earnings management as it relates to tax planning strategies, deferred tax liabilities, fluctuations in tax rates, and the repercussions of the Covid-19 pandemic is the subject of this study. Furthermore, the research examines whether corporate governance could mitigate the effects of deferred tax liabilities and tax planning on earnings management strategies. The data utilized in this study consists of 81 companies that were registered on the Indonesia Stock Exchange from 2016 to 2022. The analytical method employed in this research is Moderated Linear Regression Analysis (MRA). The findings indicate that there is a positive and statistically significant relationship between corporate governance and earnings management, as well as tax rates. However, the influence of corporate governance in mitigating the consequences of earnings management strategies involving tax planning and deferred tax obligations is minimal. It is noteworthy to mention that earnings management is not impacted by tax planning, deferred tax obligations, or the precise time frame of the COVID-19 pandemic.